2017
DOI: 10.1016/j.fcr.2017.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Retrieving LAI, chlorophyll and nitrogen contents in sugar beet crops from multi-angular optical remote sensing: Comparison of vegetation indices and PROSAIL inversion for field phenotyping

Abstract: Remote sensing has gained much attention for agronomic applications such as crop management or yield estimation. Crop phenotyping under field conditions has recently become another important application that requires specific needs: the considered remote-sensing method must be (1) as accurate as possible so that slight differences in phenotype can be detected and related to genotype, and (2) robust so that thousands of cultivars potentially quite different in terms of plant architecture can be characterized wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
86
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(98 citation statements)
references
References 66 publications
1
86
0
Order By: Relevance
“…However, data mining of hyperspectral data is limited by the number of ground‐truth photosynthetic measurements (in particular, the number of samples is less than the dimension of hyperspectral data). Second, spectral reflectance captured by a hyperspectral sensor at the canopy level is more complex and composited by multisource variability, such as those associated with plant geometry and architecture, leaf scattering properties, and background soil (Jay et al, ; Mohd Asaari et al, ). Thus, spurious spectral variations are introduced in the recorded signals, blurring spectral signatures associated with target photosynthetic traits.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, data mining of hyperspectral data is limited by the number of ground‐truth photosynthetic measurements (in particular, the number of samples is less than the dimension of hyperspectral data). Second, spectral reflectance captured by a hyperspectral sensor at the canopy level is more complex and composited by multisource variability, such as those associated with plant geometry and architecture, leaf scattering properties, and background soil (Jay et al, ; Mohd Asaari et al, ). Thus, spurious spectral variations are introduced in the recorded signals, blurring spectral signatures associated with target photosynthetic traits.…”
Section: Introductionmentioning
confidence: 99%
“…RTMs such as PROSPECT (Jacquemoud & Baret, ) and PROSAIL (Jacquemoud et al, ) have been used to characterize structural and biochemical parameters, for example, leaf area index (LAI), chlorophyll content, and dry matter content (Clevers & Kooistra, ; Darvishzadeh et al, ; Duan et al, ; Si et al, ). Jay et al () showed that the PROSAIL model, evaluated over 14 sugar beet cultivars, could well estimate LAI and chlorophyll content with root mean square error (RMSE) ≤10%. Given the close relationship between leaf characteristics (e.g., leaf pigments, structure, water, and dry mass content) and photosynthetic traits (Ceccato et al, ; Jacquemoud & Baret, ; Lobato et al, ), the reduction of hyperspectral reflectance into several meaningful biophysical parameters through RTMs may thus help identify subtle differences in photosynthetic traits among different cultivars.…”
Section: Introductionmentioning
confidence: 99%
“…At canopy level, the VIs based on VNIR bands could also be used to quantify N accumulation because it is highly related to crop biomass (Zheng et al, 2018a). Moreover, previous studies proved that the estimation of foliar biochemistry was affected by the crop canopy structure and sun-sensor geometry (Jay et al, 2017b). However, most studies still used canopy reflectance data from nadir observations, so that only the spectral information from the top layer of canopy could be considered.…”
mentioning
confidence: 99%
“…For instance, Aparicio et al [12] revealed that the performance of VIs to predict wheat yield varied with the sensor view angle. Jay et al [13] also found that the retrieval accuracy of structural and biochemical sugar beet plant traits from VIs were strongly dependent on sun-view geometry. Danner et al [14] found anisotropic effects of sensor view angle on reflectance were relatively strong for early growth stages of the winter wheat canopy, which also influenced the retrieval of the LAI based on PROSAIL model.…”
Section: Introductionmentioning
confidence: 99%